Sentidos de política e/de gestão nas pesquisas sobre a escola - Abdian, Graziela Zambão [UNESP]; Andrade, Éderson [UNESP]; Parro, Ana Lúcia Garcia [UNESP] (FapUNIFESP (SciELO), 2017)
The purpose of this article it to explore some theoretical-methodological perspectives which are found in studies about/in schools, and seeks to analyze the meaning they assign to Policy and Management. Our assumption is that there are theoretical-methodological changes in the studies whose aim is absorb the critical theory and the need to understand school life; however, there are also continuities in the way research is thought and done which provide elements that prevent them from seizing and comprehending the complexity of what is done in schools in their everyday routine. In order to achieve this purpose, an analysis is conducted in relation to three theoretical-methodological perspectives regarding the study of schools, giving rise to a new way to think the categories of Policy and Management bearing in mind above all the management policies that can be found in Brazilian public schools. The challenge is to see the field of school management as the one which produces and (re)produces management policies, taking into account mainly that, in the production of policies, there is an ongoing flow of negotiations between the political meanings of human action. Finally, we conclude that, based on this way of thinking, it might be possible to expand the theoretical-methodological field of the area, touching other ways of producing knowledge other than the school management as the mediator of a given educational policy.
Policy and management meanings in the research about schools
Keywords: Educational policy and management; Everyday routine; School